"Which door should I go through?" (In)visible intersections of race and disability in the academy. Issue 4 (7th April 2019) - Bhakta, Amita
Abstract : Institutional inclusivity and diversity have been an increasing focus of debate within the academy. For the discipline of geography and universities more broadly to become fully inclusive, greater attention is warranted within these debates on the intersection of race and disability. An existing lack of discussion on relations between race and disability in the academy draws attention to the invisibility of disabled academics of black and minority ethnic backgrounds. Drawing on examples of spaces of (mis)recognition and of indifference inside and outside the space of the British academy, this paper calls for greater attentiveness in geography and beyond to the socio‐cultural and spatial issues faced by ethnic minority disabled members of the university community that are otherwise hidden. A focus on these hidden issues in research agendas, institutional practices, and the academy more broadly is warranted to enable the university to strive towards greater inclusivity. Abstract : Drawing on examples of spaces of (mis)recognition and of indifference inside and outside the space of the British academy, this paper calls for greater attentiveness in geography and beyond to the socio‐cultural and spatial issues faced by ethnic minority disabled members of the university community that are otherwise hidden. A focus on these hidden issues in research agendas, institutional practices, and the academy more broadly is warranted to enable the university to strive towards greater inclusivity.